The Role of Good Corporate Governance in Enhancing Corporate Accountability: A Systematic Literature Review - Afsha Harnia; Aisyah Nurhaliza Arifin; Rizky Natasya; Siti Khairunnisa; Zahira Naswa Ramadani; Neng Sri Wardhani (Yayasan Multidimensi Kreatif, 2026)
The implementation of Good Corporate Governance (GCG) has become a strategic issue within the Indonesian corporate landscape, particularly in light of the increasing number of corruption cases and instances of weak accountability at major companies such as PT Jiwasraya, PT Timah, and PT Pertamina, which have caused state losses amounting to hundreds of trillions of rupiah. This study aims to analyze the role of GCG in enhancing corporate accountability through a Systematic Literature Review (SLR) approach. Data were collected by searching for scientific journal articles in the Google Scholar, Garuda, and Sinta databases published between 2021 and 2026, using the keywords